EFEK PELATIHAN DAN KOMPETENSI TRAINER TERHADAP PENINGKATAN KUALITAS TENAGA KERJA DI KABUPATEN SUMBAWA - Sumbawati, Novi Kadewi; Rahim, Abdul; Putri, Amelia (Samalewa: Jurnal Riset & Kajian Manajemen, 2025)
This study aims to determine the effect of training and trainer competence on the quality of the workforce in Sumbawa District. The type of this study used was associative study to examine the effect of training (X1) and trainer competence (X2) on the quality of the workforce (Y), both partially and simultaneously. The type of data used in this study was quantitative data obtained directly from primary sources using questionnaires. The data source in this study was all job training participants at Dinas Tenaga Kerja dan Transmigrasi of Sumbawa District, totaling 52 people, who were determined using probability sampling techniques with the simple random sampling method. The data analysis techniques used include multiple linear regression analysis, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination testing (R2). The results of this study showed that training (X1) and trainer competence (X2) had a positive and significant effect on the quality of the workforce in Sumbawa District (Y), both partially and simultaneously. The degree of effect of training (X1) and trainer competence (X2) on the quality of the workforce in Sumbawa District (Y) was 37.4%, while the remaining 62.6% is effected by other variables not examined in this study, such as work motivation, work facilities, compensation and work environment.